The big four eaudiobook - Christie, Agatha (Hercule Poirot, 2012)
Famed private eye Hercule Poirot tackles international intrigue and espionage in this classic Agatha Christie mystery. Framed in the doorway of Hercule Poirot's bedroom stands an uninvited guest, coated from head to foot in dust. The man stares for a moment, then he sways and falls. Who is he? Is he suffering from shock or just exhaustion? Above all, what is the significance of the figure 4, scribbled over and over again on a sheet of paper? Poirot finds himself plunged into a world of international intrigue, risking his life—and that of his ""twin brother""—to uncover the truth.